Tripterygium hypoglaucum (Lévl.) Hutch and Its Main Bioactive Components: Recent Advances in Pharmacological Activity, Pharmacokinetics and Potential Toxicity - Zhao, Junqi; Zhang, Fangling; Xiao, Xiaolin; Wu, Zhao; Hu, Qichao; Jiang, Yinxiao; Zhang, Wenwen; Wei, Shizhang; Ma, Xiao; Zhang, Xiaomei (Frontiers in Pharmacology, 2021)
Tripterygium hypoglaucum (Lévl.) Hutch., a plant widely distributed in the Yunnan, Guizhou, and Sichuan regions and other places in China, exhibits prominent medicinal bioactivities. Phytochemical studies have led to the discovery of 120 secondary metabolites in this genus, and previous studies have found that Tripterygium hypoglaucum (Lévl.) Hutch. contains terpenoids, alkaloids, glycosides, sugars, organic acids, oleanolic acid, polysaccharides, β-sitosterol and other components. In recent research, Tripterygium hypoglaucum (Lévl.) Hutch. was proved with various pharmacological effects containing antifertility, anti-tumor and immunosuppression effects. As for the bioactivity in compounds, diterpenes and alkaloids are the main active components responsible for the pharmacological activities of this genus, including anti-inflammation, immunosuppression, anti-tumor, anti-obesity, insulin resistance and anti-fertility effects. Triptolide and celastrol are the main active ingredients of Tripterygium hypoglaucum (Lévl.) Hutch. . Their mechanisms involve inhibiting the pro-inflammatory factors interleukin-6 (IL-6), tumour necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) by regulating the nuclear factor kappa-B (NF-κB) signalling pathway. However, the side effect of Tripterygium hypoglaucum (Lévl.) Hutch. is also the problem for its application. A series of reports indicated that multiple organs and systems were involved in the toxicity. Furthermore, the most serious side effects are closely related to the liver. Long-term treatment with Tripterygium hypoglaucum (Lévl.) Hutch. downregulated the mRNA and protein expression of the steroidogenic acute regulatory protein (StAR), P450 side-chain cleavage enzyme (P450scc), cytochrome P450 17-hydroxylase (P450c17), 3β-hydroxysteroid dehydrogenase (3β-HSD), and 17β-hydroxysteroid dehydrogenase (17β-HSD). Considering the effect and toxicity of the compounds found in this plant, the compounds might be developed into promising agents via modern technical methods.